2020
DOI: 10.3390/vaccines8020196
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Live Attenuated Influenza Vaccine Viruses Carrying Conserved T Cell Epitopes of Human Adenoviruses Induce Functional Cytotoxic T Cell Responses and Protect Mice against both Infections

Abstract: Human adenoviruses (AdVs) are one of the most common causes of acute respiratory viral infections worldwide. Multiple AdV serotypes with low cross-reactivity circulate in the human population, making the development of an effective vaccine very challenging. In the current study, we designed a cross-reactive AdV vaccine based on the T-cell epitopes conserved among various AdV serotypes, which were inserted into the genome of a licensed cold-adapted live attenuated influenza vaccine (LAIV) backbone. We rescued t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…Here, we explored the possibility of licensed live attenuated influenza vaccine backbone as a viral vector to deliver additional conserved M2e epitopes of influenza A viruses to the target cells to enhance the breadth of protection afforded by classical LAIV viruses. It is well known that LAIVs induce cross-reactive immunity with a potential to protect against drifted influenza viruses in a variety of animal models as well as in human trials [ 15 , 42 , 43 , 44 ], and numerous studies have proven that LAIV is a promising viral vector for designing vaccines against other infectious pathogens [ 45 , 46 , 47 , 48 ]. Our recent study demonstrated that seasonal H1N1 and H3N2 LAIVs expressing four M2e tandem repeats within the chimeric HAs can elicit M2e-specific antibody and, to a lesser extent, T-cell responses which enhanced cross-protective potential of the vaccines [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here, we explored the possibility of licensed live attenuated influenza vaccine backbone as a viral vector to deliver additional conserved M2e epitopes of influenza A viruses to the target cells to enhance the breadth of protection afforded by classical LAIV viruses. It is well known that LAIVs induce cross-reactive immunity with a potential to protect against drifted influenza viruses in a variety of animal models as well as in human trials [ 15 , 42 , 43 , 44 ], and numerous studies have proven that LAIV is a promising viral vector for designing vaccines against other infectious pathogens [ 45 , 46 , 47 , 48 ]. Our recent study demonstrated that seasonal H1N1 and H3N2 LAIVs expressing four M2e tandem repeats within the chimeric HAs can elicit M2e-specific antibody and, to a lesser extent, T-cell responses which enhanced cross-protective potential of the vaccines [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here, the transgene is not present in the viral particle, but should be translated within the infected cell, because the NS1 protein is abundantly expressed in the early stages of infection [ 29 ]. Such modification of LAIV genome has been previously shown as a promising strategy for the induction of robust cytotoxic T-cell responses to the inserted immunodominant CD8 T-cell epitope of a foreign pathogen [ 30 , 31 , 32 ]. In vitro studies confirmed that regardless of how the 4M2e cassette was inserted into the LAIV genome, M2e proteins were expressed at significantly higher levels when mammalian cells were infected with the LAIV+4M2e recombinant candidates than with the classic LAIV strain, demonstrating the LAIV’s ability to properly deliver additional M2e antigens to target cells.…”
Section: Discussionmentioning
confidence: 99%
“…To assess T-cell responses to influenza A virus, an intracellular cytokine staining (ICS) assay was performed as previously described [ 29 ]. Briefly, splenocytes were isolated 5 days after the influenza A virus challenge according to the design of the experiment described in Section 2.5 .…”
Section: Methodsmentioning
confidence: 99%